Genomic basis of endosymbiont-conferred protection against an insect parasitoid - Hansen, Allison K.; Vorburger, Christoph; Moran, Nancy A.

(untitled) (Genome Research, 2012)
Bacterial endosymbionts exert a variety of beneficial effects on insect hosts. In pea aphids (Acyrthosiphon pisum), several inherited endosymbiont species protect their hosts against parasitoid wasps, which are major natural enemies. However, strains of these symbiont species vary in their ability to confer protection against parasitoids, with some conferring almost complete protection and others conferring almost none. In this study, two strains of the endosymbiont Regiella insecticola (R. insecticola 5.15 and R. insecticola LSR1) were found to differ in ability to protect pea aphids attacked by the parasitoid Aphidius ervi. Parasitism trials reveal that R. insecticola 5.15, but not R. insecticola LSR1, significantly reduced parasitoid success and increased aphid survivorship. To address the potential genetic basis of protection conferred by R. insecticola 5.15 we sequenced the genome of this symbiont strain, and then compared its gene repertoire with that of the already sequenced nonprotective strain R. insecticola LSR1. We identified striking differences in gene sets related to eukaryote pathogenicity. The protective strain R. insecticola 5.15 encoded five categories of pathogenicity factors that were missing or inactivated in R. insecticola LSR1. These included genes encoding the O-antigen biosynthetic pathway, an intact Type 1 Secretion System and its secreted RTX toxins, an intact SPI-1 Type 3 Secretion System and its effectors, hemin transport, and the two-component system PhoPQ. These five pathogenicity factors and translocation systems are hypothesized to collectively play key roles in the endosymbiont's virulence against parasitoids, resulting in aphid protection. Mechanisms through which these factors may target parasitoids are discussed.